The impact of the Great War on French regionalism 1900-1924 - Cudbird, TJ (2020)
Many Radical politicians believed that the regionalist programme, including regional assemblies, was a threat to the Third Republic. It implied a return to a traditional society, based on the provinces of the Ancien Régime and under the influence of the Catholic church. It might encourage separatism in areas with a different culture and language. This view set an interpretative framework for the historiography of French regionalism. Such a framework is open to question because it ignores a more pragmatic strand of regionalism which developed just before the Great War and which saw a shift of power to regional elites and their institutions as a way of modernising the French economy. This was a regionalism wholly compatible with Republican values.